Urban design concepts of ruins in Gdańsk historical area - Kowalska, Agnieszka (Protection of Cultural Heritage, 2018)
The Gdańsk Downtown which now consists of several historical districts, has been extensively damaged during the World War II. Early after the War, in the 40’s first restoration concepts have been applied in one of representative districts - today’s Main City. The urban design included exact historical reconstruction of all public facilities and well historically documented housing. The other buildings have been planned in historical - post-medieval manner. In other Downtown areas only public facilities were designed within the historical concept, housing and groceries were built according to recent (post War) ideas. In the center of Downtown, remain the area of Granary Island with several granaries and some collapsed historical storages preserved after the World War II. In the years 2012-2014 new designs for Granary Island area have been approved in local urban planning concepts. In some parts of the Island, for example in northern part, this process is still in progress. The new architectural idea, which is planned for applying in cases of granaries called Daleka Droga, Arka Noego, Czarny Kogut i Kuźnia will considered superstructure over the historical remains. Two ways of architectural designs of superstructures are contemplated, one with use of historical elements, the other with use of modern materials, especially glass.